A magyar szociológia centenáriuma - Saád, József (Szociológiai Szemle, 2024)
The beginnings of the professional sociology in Hungary goes back to January 1900, the first issue of the Huszadik Század (Twentieth Century) and to January 1901, the foundation of the Társadalomtudományi Társaság (Society of Social Sciences), the first community of Hungarian social thought and science. The 100th anniversary is an occasion for remembering the main characteristics, the greatest representatives and the outstanding achievements of the first period, that of the two decades of the last century in the history of the Hungarian sociology. The remembrance focuses on the great sociological theories, and attempts to understand and conceptualise the main social processes of the turn of the century. The author emphasises the impact of the political approaches on sociological thought. Providing an overview of the Huszadik Század, he calls attention to the importance of this periodical in the Hungarian cultural history.